LWMPI: An MPI library for NoC‐based lightweight manycore processors with on‐chip memory constraints - Uller, João Fellipe; Souto, João Vicente; Penna, Pedro Henrique; Castro, M.; Freitas, H.; Méhaut, Jean-François; Penna, Pedro Henrique (Concurrency and Computation: Practice and Experience, 2021)
Lightweight manycore processors deliver high performance and energy efficiency by bundling hundreds of low‐power cores, a distributed memory architecture with small local memories and Networks‐on‐Chip in a single die. However, the lack of rich and portable programming models for these processors makes software development a challenging task. Currently, two approaches are employed to address programmability in lightweight manycores: Operating Systems (OSes) and baremetal runtime libraries. The former provides portability but exposes complex Operating System (OS)‐level programming interfaces to developers. The latter focuses on providing rich and high performance interfaces, which are vendor‐specific and yield to non‐portable software. In this work, we address these programmability and portability challenges by combining a rich OS with a well‐known standard for parallel programming. We propose a portable and lightweight Message Passing Interface (MPI) library (LWMPI) designed from scratch to cope with restrictions and intricacies of lightweight manycores. We integrated LWMPI into Nanvix, an open‐source distributed OS that runs on silicon lightweight manycores. The results obtained with a synthetic benchmark and a subset of the CAP Bench applications running on Kalray MPPA‐256 unveil that LWMPI not only delivers a lightweight and richer programming interface but also presents good performance and scalability results.